2009
DOI: 10.1016/j.cll.2009.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Viruses in Bronchiolitis and Their Link to Recurrent Wheezing and Asthma

Abstract: Bronchiolitis is the leading cause of hospitalization for children age <1 year and these hospitalized children have an increased risk of developing childhood asthma. It remains unclear, however, which children with severe bronchiolitis (e.g., an episode requiring hospitalization) will develop recurrent wheezing and/or asthma. Although many environmental and genetic factors may play a role in the pathway from bronchiolitis to asthma, this review focuses on the viruses that have been linked to bronchiolitis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0
8

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 147 publications
2
26
0
8
Order By: Relevance
“…Many studies have proposed that vitamin D concentration decreases due to the decrease in sunlight during the winter months, resulting in a related decrease in immune functions and sensitivity to influenza infections (12,13).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have proposed that vitamin D concentration decreases due to the decrease in sunlight during the winter months, resulting in a related decrease in immune functions and sensitivity to influenza infections (12,13).…”
Section: Discussionmentioning
confidence: 99%
“…Recent vitamin D studies suggest that low levels of 25(OH)D are associated with increased risk of lower respiratory tract infections, wheezing illnesses and asthma in young children. 8,9 In addition, some observational studies reported that increased vitamin D in maternal diet may reduce the risk of recurrent wheezing. 10,11 Upper respiratory tract infections account for more than 80% of wheezing episodes in children.…”
Section: Discussionmentioning
confidence: 99%
“…Second, we can consider risk modulators such as using palivizumab and emerging novel immunomodulatory therapies on these patients to help prevent RSV infections. Third, we can route these patients into future randomized clinical trials to advance bronchiolitis and asthma prevention research [207]. Fourth, by distinguishing early asthma patients from transient early wheezers, clinicians can better manage early wheezers [208].…”
Section: Predicting Whether a Bronchiolitis Patient Will Later Be Diamentioning
confidence: 99%
“…The model achieved a low sensitivity of 65%, a specificity of 82%, a low positive post-test probability around 50%, and a low negative post-test probability around 11%. At present, no predictive model for asthma diagnosis can attain satisfactory accuracy [206,207].…”
Section: Predicting Whether a Bronchiolitis Patient Will Later Be Diamentioning
confidence: 99%